2019
DOI: 10.1007/s12178-019-09592-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Ankle Lateral Ligament Stabilization

Abstract: Purpose of Review Ultrasound (US) is an increasingly popular imaging modality currently used both in clinics and operating rooms. The purpose of this review is to appraise literature describing traditional lateral ankle stabilization techniques and discuss potential advantages of US-guided ankle lateral ligament stabilization. In addition, albeit limited, we will describe our experiences in perfecting this technique. Recent Findings To date, the modified open Broström-Gould technique remains as the gold standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Finally, knot tying was performed for tensioning the ATFL with the ankle at a neutral plantarflexion-dorsiflexion position. 17 Additional arthroscopic procedures and/or open procedures were performed in cases where intra-articular lesions, such as symptomatic os trigonum, osteochondral lesions, loose bodies, or impinging osteophytes, and peroneal tendon lesions were clinically suspected in addition to CAI ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, knot tying was performed for tensioning the ATFL with the ankle at a neutral plantarflexion-dorsiflexion position. 17 Additional arthroscopic procedures and/or open procedures were performed in cases where intra-articular lesions, such as symptomatic os trigonum, osteochondral lesions, loose bodies, or impinging osteophytes, and peroneal tendon lesions were clinically suspected in addition to CAI ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The potential advantages suggested were the microinvasive nature of the procedure, the safety to nearby neurovascular structures, and the procedural accuracy ( Figure 1 ). 17 However, to our knowledge, no previous reports have examined the anatomic accuracy of the anchor position in sonographically guided ATFL repair.…”
mentioning
confidence: 98%
“…Under US guidance, the curved tip of the MicroSutureLasso Minor Bend was introduced into the ATFL stump. 12 After the ATFL, subcutaneous tissue, and skin were penetrated, a nitinol loop wire was deployed. Next, upon visualization of the long axis of the ATFL, the MicroSutureLasso Minor Bend was inserted into the talar stump of the ATFL.…”
Section: Methodsmentioning
confidence: 99%
“…A suture anchor (DEX Fibertak; Arthrex) was placed at the anatomic fibular footprint after insertion of the drill guide followed by drilling under US guidance. 12 The 4 limbs of the nitinol wires were retrieved subcutaneously through the anchor incision below the superior peroneal nerve and above the ATFL. Each nitinol loop was relayed to each limb of the suture anchor, and 2 limbs of the suture anchor were clamped.…”
Section: Methodsmentioning
confidence: 99%
“…In the eld of orthopaedics, accurate positioning and navigation during surgery are particularly important; otherwise, nerve and blood vessel damage and other postoperative complications will be caused, leading to poor prognosis of patients. For example, in lateral ankle stabilization techniques, ultrasound-guided arthroscopy can make the direct visualization of ankle anatomical landmarks and structures possible and can also effectively reduce surgical time and decrease the incidence of iatrogenic damage to neurovascular and other soft tissue structures (39). Similarly, Yang et al conducted a randomized controlled study in which ultrasound-mediated anaesthesia was used in 38 patients who needed surgery on the ankle joint and not in another 38; they found that the use of ultrasound results in fewer complications, which points out the direction of the development of ultrasound in treatment.…”
Section: Research Focused On Ultrasound In Orthopaedicsmentioning
confidence: 99%